Efforts in Community Empowerment through Coinization Fund Collection in Ngronggot Village, Ngronggot District, Nganjuk Regency - Arifin, Zainal; Sujoko , Sujoko; Asmoro , Nur; Khoiriyah , Anatul; Binti Rosyidah (STAI Miftahul ULa Nganjuk, 2023)
This study explores the efforts in community empowerment through the coinization fund collection model in Ngronggot Village, Ngronggot District, Nganjuk Regency. The initiative aimed to enhance local economic self-reliance by leveraging community assets and fostering collective action. Using the Asset-Based Community Development (ABCD) approach, the research highlights the active participation of villagers, transparent financial management, and the strengthening of social cohesion. The study also examines the role of local leadership in ensuring the sustainability and effectiveness of the fund collection process. The findings indicate that the coinization model has positively impacted community engagement, financial inclusion, and local governance. However, challenges related to inclusivity and the long-term viability of the initiative remain, necessitating continuous adaptation and community involvement. The research contributes to the broader understanding of community-driven development models and their potential for fostering sustainable socio-economic transformation.